Effect of water table depth on the survival and productivity of rubber (Hevea brasiliensis) plantations under the risk of climate variability - Brenes-Bonilla, Fanny (2026)
The availability of water in the soil is a critical factor for the development and survival of forest plantations, including forest crops such as Hevea brasiliensis (natural rubber). Complementing the study of the major factors that influence forest productivity, this research emphasizes the hydric and pedological properties and their influence on the establishment and growth of such crops. This paper presents the methodological approach and initial results of a hydropedological analysis that considers physical soil parameters such as texture, bulk density, total porosity, hydraulic conductivity, and moisture retention curves, which reflect how the soil retains and mobilizes water available to roots. There are very few studies in forest plantations that assess the evolution of the soil profile and forest management practices (such as thinning, pruning, or latex extraction) and their effects on water retention capacity and availability. Furthermore, soil chemistry — including pH, exchangeable aluminum, total carbon and nitrogen, cation exchange capacity, and base saturation — correlates with fertility and water-holding capacity, both fundamental factors for productivity and drought resistance in Hevea brasiliensis. Recent research conducted in rubber tree plantations in Costa Rica indicates that the pedological evolution of soils in areas such as Guácimo and Siquirres, Limón (Costa Rica) helps to understand how these physical and chemical variables interact to either enhance or limit the early stages of vegetative development. Studying these interactions is a key element for anticipating other effects related to climatic variability and excessive or deficient soil moisture.